THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE (Study At PT. Indo Bismar) - Moh Mukhrojin (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
The purpose of this study was to determine the relationship or relationship between organizational culture and the performance of employees of PT. Indo Bismar Surabaya. To find out the organizational culture and employee performance at PT. Indo Bismar Surabaya. To analyze and measure how much influence organizational culture has on employee performance at PT. Indo Bismar Surabaya. This study uses a quantitative approach, namely research that presents a further stage of observation. After having a set of classification schemes, the researcher then measures the size or distribution of these traits among members of a particular group. Based on the results of the research and discussion that has been stated, it can be concluded that between culture and employee performance at PT. Indo Bisma has a significant positive relationship. The existence of this positive relationship is known from the results of proving the hypothesis which shows a correlation of 0.480 with a probability of 0.000 (p <0.05), which means that the proposed hypothesis can be accepted. The existence of this positive relationship is also supported by the coefficient of determination of 0.230, it can be said that organizational culture provides an effective contribution of 23% to the performance of employees at PT. Indo Bismar Surabaya.